PENGARUH PERBEDAAN SUHU TERHADAP PERTUMBUHAN BENIH IKAN MAS KOI (Cyprinus carpio) (The influence of the temperature against the growth of the seed goldFish koi (Cyprinus carpio) - Emaliana Emaliana; Syammaun Usman; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
One of the constraints in the effort coltivation koi fish is the level of survival rates low and the growth of fish relatively slow caused by the temperature is not stable, then koi fish become stress later died. This study was aimed to determine how big effect the temperature against the growth of the seeds of goldfish koi and to know the best temperature for the growth of the seeds of goldfish koi. The experimental design used is Completely Randomized Design (CRD) with four treatment and three test. The artificial fish fed as much as twice a day during the study 09.00 and 18.00. turn of the water as much as 10 % of the volume total of water. An early stage before done maintenance is the process of the adaptability for 30 minutes. Fish maintained for 30 days and every 10 days done measurement was covering long total, heavy and survival rates of fish. Measures of the quality of the water is temperature, pH and DO. The seeds of koi fish that maintained at a temperature 270C growth long absolute necessity of 11,74 cm and growth of weight range 8,61 - 10,36 gr. The value of survival rate is 100%. Parameters supporters quality of water oftained from pH changed 7,08 – 7,15 and DO changed 5,22 -5,61 mg/l. The temperature is maintenance koi fish still in a state of optimally that at temperature 270C. The treatment is temperature showed a significant effect against the growth of long and weights of koi fish and range of temperature for live of koi fish betweer 26-31oC but the best temperature for the growth is 27oC.Keywords: Temperature, The seeds of goldfish Koi, Growth, The survival